Uji Efektivitas Ekstrak Umbi Bit (Beta vulgaris) Terhadap Kontrol Gula Darah dan Gambaran Histopatologi Pankreas Pada Tikus Diabetes Yang Diinduksi Aloksan - Brahmana, Lisa Charolin Br; Angie, Evelyn; Lister, Gilbert (Riviera Publishing, 2025)
Diabetes mellitus is a metabolic disease characterized by increased blood sugar levels due to the body's inability to process insulin. The disease can affect a variety of organs, including the eyes, kidneys, heart, and nervous system. This study aims to evaluate the effect of ethanol extract of beet tubers on the decrease in blood sugar levels and changes in the histopathology of the pancreas. Through a true experiment design with the pretest-postest group in aloxan-induced wistar rats, the animals were divided into six groups: the normal, negative control, positive control (metformin) groups, and three treatment groups with beet tuber extract at doses of 22.5 mg/kgBB, 45 mg/kgBB, and 90 mg/kgBB. Blood glucose levels were measured on days 0, 3, 6, 9, 12, and 14. Results showed a significant difference between day-0 and day-14 (P <0.05), but there was no significant difference between the positive control group and all treatment groups (P > 0.05). Histopathology shows beet tuber extract and metformin do not provide a significant difference to the pancreas. Beet tuber extract is effective as an antidiabetic in lowering blood sugar levels in aloxan-induced rats.